Discrete PIDx(n-2) Stage PD Cascade Controllers Proposed by Kitti - Suralak Charoonsote; Prapart Ukakimaparn; Pittaya Pannil; Thanit Trisuwannawat (My University, 2016)
A Proportional-Integral-Derivative (PID)Controller has only two zeros and not enough for most industrial plants thatare third or higher order plant. To achieve the desired specifications by PIDcontrols, Associate Professor Dr. Kitti Tirasesth proposed the way to add morezeros to the PID controller according to the order of the plant. By thistechnique, the designer find only two unknown parameters based on the rootlocus magnitude and angle conditions. By increasing only the controller gain,the faster response with smaller overshoot can be obtained. Now thediscrete-time proposed controllers are ready for real time implementation.
Keywords: Overshoot (microwave communication); Rise time; Advanced Control Systems Optimization